The Dirichlet problem for −Δφ=e−φ in an infinite sector. Application to plasma equilibria. (June 2015) - Goubet, Olivier; Labrunie, Simon
Abstract: We consider here a nonlinear elliptic equation in an unbounded sectorial domain of the plane. We prove the existence of a minimal solution to this equation and study its properties. We infer from this analysis some asymptotics for the stationary solution of an equation arising in plasma physics.